2022
DOI: 10.1155/2022/4254631
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Classification from Chest X-Ray Images: A Framework of Deep Explainable Artificial Intelligence

Abstract: COVID-19 detection and classification using chest X-ray images is a current hot research topic based on the important application known as medical image analysis. To halt the spread of COVID-19, it is critical to identify the infection as soon as possible. Due to time constraints and the expertise of radiologists, manually diagnosing this infection from chest X-ray images is a difficult and time-consuming process. Artificial intelligence techniques have had a significant impact on medical image analysis and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…Speaking of hybrid ML models, a hybrid model proposed by Ravi et al [ 12 ] exhibits improved performance in terms of efficiency, because the model uses only critical features for its training. For this purpose, a combination of feature selection algorithms and fuzzy systems has been utilized.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Speaking of hybrid ML models, a hybrid model proposed by Ravi et al [ 12 ] exhibits improved performance in terms of efficiency, because the model uses only critical features for its training. For this purpose, a combination of feature selection algorithms and fuzzy systems has been utilized.…”
Section: Related Workmentioning
confidence: 99%
“…It was demonstrated that the model performs more efficiently when fewer but more relevant features are used. To further improve the performance of the model, another feature selection, and extraction method, i.e., the Principal Component Analysis (PCA) was also incorporated [ 12 ]. Similarly, Khan et al [ 13 ] improved the learning performance by using various derivations of decision trees, including Fuzzy Decision Trees (FDT), Hybrid Decision Trees (HDT), and other related fuzzy rules to estimate the rate of recurrence for the breast cancer patients.…”
Section: Related Workmentioning
confidence: 99%
“…The trained model achieves 72% accuracy, which is higher than the recent methods. Khan et al (31) presented a DL and explainable AI-based framework for COVID-19 classification from CXR images. Transfer learning was utilized to train pretrained deep models on enhanced images, and features were merged for greater information.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning is a machine learning technology that uses multilayer convolutional neural networks (CNNs) [11]. It has a significant effect in fields associated to medical imaging such as brain tumor detection as in [12] which proposes a fully automated design to classify brain tumors, COVID-19 as in [13,14] which propose a deep learning and explainable AI technique for the diagnosis and classification of COVID-19 using chest X-ray images and [14] which proposed a CNN-LSTM and improved max value features optimization framework for COVID-19 classification to address the issue of multisource fusion and redundant features, lung cancer [15], which developed and validated a deep learning-based model using the segmentation method and assessed its ability to detect lung cancer on chest radiographs, etc.…”
Section: Introductionmentioning
confidence: 99%